Early Childhood Education and Development in Nepal: Status, Trends and Challenges - Shrestha, Dhurba Kumar (DMC Journal, 2023)
Early Childhood Education and Development (ECED) is considered as foundations of modern education system in Nepal. It's the preparedness of children for school in terms of their physical growth, mental capacities, and social adjustment. Over the last two decades, some notable achievements have been achieved beside low investment by the government in ECED sectors in Nepal. The average ECED gross enrollment rate have reached at 89.62 per cent and achieved attractive progress in gender (0.92) parity in ECED. However, community-based ECEDs in geographically remote area are running without basic requirements. An execution of Local Government Operation Act-2017 (LGRG) and School Education Sector Plan (2022-32) contributing to strengthen the ECED in Nepal. Inadequate investment, insufficient ECEDs, absence of skilled and permanent ECED facilitator, dissimilarities between ECEDs, lack of friendlier infrastructure, complexities to implement bilingual curriculum, inaccessible and unaffordable education system, existence of dual education system, and structural discriminations are still observed as unsolved issues. This paper tries to review the status, trends and challenges associated to Early Childhood Education Development in Nepal.